Precision medicine approaches for the management of Ewing sarcoma: current perspectives - Rizk VT; Walko CM; Brohl AS (Dove Medical Press, 2019)
Victoria T Rizk,1 Christine M Walko,2 Andrew S Brohl3,41University of South Florida Hematology/Oncology Fellowship, 2DeBartolo Family Personalized Medicine Institute, 3Sarcoma Department, 4Chemical Biology and Molecular Medicine Program, H. Lee Moffitt Cancer Center and Research Institute, Tampa, FL, USA Abstract: Advancements in molecular and genetic techniques have significantly furthered our biological understanding of Ewing sarcoma (ES). ES is typified by a driving TET–ETS fusion with an otherwise relatively quiet genome. Detection of one of several characteristic fusions, most commonly EWSR1–FLI1, is the gold standard for diagnosis. We discuss the current role of precision medicine in the diagnosis, treatment, and monitoring of ES. Continued efforts toward molecularly guided approaches are actively being pursued in ES to better refine prognosis, identify germline markers of disease susceptibility, influence therapeutic selection, effectively monitor disease activity in real time, and identify genetic and immunotherapeutic targets for therapeutic development. Keywords: Ewing sarcoma, next generation sequencing, genomics, liquid biopsy, targeted therapy